Suffering as Reflected in Charles Dickens’ Oliver Twist - Tini Mogea (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is to find out the suffering of Oliver, Charles Dicken’s Oliver Twist. This research is qualitative since the data are in the form of words rather than numbers. The data were collected in the novel Oliver Twist, which was the primary source. The secondary sources, such as books, documents, and the internet, are used to support the analysis. An objective approach was applied in analyzing the data.The result shows that suffering changes Oliver and has a range of impacts. His suffering comes in physical and mental forms. The physical suffering is physical violence, which among others is beating; besides physical suffering, he also had mental suffering, which were depression, intimidation, painfulness, etc. The physical pain that Twist received made him lose too much weight, and he turned into a thin boy. He became an orphan as a result of his mistreatment. Mentally, Twist becomes someone who is easily touched and emotionally moved; he also turns into a wild child. The causes and effects that make Oliver a thief are depression and going wild. The lack of attention and affection made Oliver think that whatever Fagin gave him was a form of attention and affection.